Long Noncoding RNAs in the Regulation of Asthma: Current Research and Clinical Implications - Zhu, Xueyi; Wei, Ying; Dong, Jingcheng (Frontiers in Pharmacology, 2020)
Asthma is a chronic airway inflammatory disorder related to variable expiratory airflow limitation, leading to wheeze, shortness of breath, chest tightness and cough. The characteristic features of asthma include airway hyperresponsiveness (AHR), airway inflammation and airway remodeling. Pathogenesis of asthma remains extremely complicated and the detailed mechanisms have not been clarified until now. Long non-coding RNAs (lncRNAs) have been reported to play prominent roles in asthma, and function as regulators of various aspects in pathological progress. In this review, we summarized recent advances of lncRNAs in the pathogenesis of asthma, which include their regulatory functions in the T helper (Th) 2 inflammation, Th17 inflammation, eosinophils (EOS) abundances, macrophage polarization, airway smooth muscle cells (ASMCs) proliferation and hormone sensitivity, to provide guidance for clinical treatment and drug development.